Long‐term regional control in the observed neck following definitive chemoradiation for node‐positive oropharyngeal squamous cell cancer. Issue 5 (29th March 2013) - Goenka, Anuj; Morris, Luc G.T.; Rao, Shyam S.; Wolden, Suzanne L.; Wong, Richard J.; Kraus, Dennis H.; Ohri, Nisha; Setton, Jeremy; Lok, Benjamin H.; Riaz, Nadeem; Mychalczak, Borys R.; Schoder, Heiko; et al.
<x xml:space="preserve">Abstract</x> Traditionally, patients treated with chemoradiotherapy for node‐positive oropharyngeal squamous cell carcinoma (N+ OPSCC) have undergone a planned neck dissection (ND) after treatment. Recently, negative post‐treatment positron‐emission tomography (PET)/computed tomography (CT) imaging has been found to have a high negative predictive value for the presence of residual disease in the neck. Here, we present the first comprehensive analysis of a large, uniform cohort of N+ OPSCC patients achieving a PET/CT‐based complete response (CR) after chemoradiotherapy, and undergoing observation, rather than ND. From 2002 to 2009, 302 patients with N+ OPSCC treated with 70 Gy intensity‐modulated radiation therapy and concurrent chemotherapy underwent post‐treatment clinical assessment including PET/CT. CR was defined as no evidence of disease on clinical examination and post‐treatment PET/CT. ND was reserved for patients with <CR on either PET/CT, clinical examination, or other imaging. 260 patients (86.1%) had clinical and radiographic CRs, and underwent neck observation (rate of regional control, 97.7%; 5‐year overall survival, 79.8%). The four observed patients experiencing neck recurrence had initial staging of N1 (n = 2), N2b (n = 1), and N2c (n = 1). Three of four were successfully surgically salvaged. There was no association between N stage and rate of neck recurrence (p = 0.74). 52 and 25% of patients undergoing ND had viable tumor in the neck after positive and negative PET/CT, respectively. We conclude that patients achieving CRs after chemoradiation, based on clinical and PET/CT assessment, have a high probability of regional control, with a 2.3% regional failure rate, and may be safely observed without planned ND.